Problems of Categorization in Comparative Typology - Avazova Lobar Buriyevna; Toshpulatova Iroda Mirmuhsin qizi (Scientific Trends, 2025)
Comparative typology is a branch of linguistics aimed at identifying common and distinctive features of languages through systematic comparison. Central to this field is the categorization of languages based on grammatical, lexical, phonological, and syntactic criteria. However, this categorization process encounters several challenges. These include the unique characteristics of individual languages, difficulties in distinguishing between universal and language-specific features, diversity of theoretical frameworks, and terminological inconsistencies. Additionally, limited linguistic data and the subjective nature of criteria complicate research efforts. This paper provides a comprehensive analysis of categorization problems in comparative typology and proposes theoretical and methodological approaches to address them. The potential of modern computational linguistic tools to assist in resolving these issues is also discussed.
Keywords: Comparative typology, categorization, grammatical category, linguistic typology, language features, theoretical approaches, terminology, computational linguistics.